The role of the principal in improving teacher performance through academic supervision - Tri Yudha Silalahi; Nirmala Adhi Yoga Pambayun; Rina Safitri (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
Teacher performance plays an important role in improving the quality of human resources, and academic supervision by the principal is one of the factors that supports this improvement. This study aims to describe the role of principals in improving teacher performance through academic supervision at SMA Negeri 1 Pangkalanbaru. This study uses a qualitative descriptive approach with the principal as the main informant and 29 teachers as supporting informants. Data were collected through questionnaires and classroom observations, then analyzed through data organization, interpretation, and verification. The results show that the academic supervision carried out by the principal received an average score of 87.37 in the “Very Good” category, indicating that the supervision was carried out in a planned and structured manner through scheduling, classroom observation, the use of standard instruments, and the provision of constructive feedback. Teacher performance also received an average score of 85.56 in the “Very Good” category, indicating that teachers were able to plan and implement learning, use varied methods and media, and evaluate learning well. However, some teachers still needed improvement in the areas of innovation, application of supervision results, and discipline. This study concludes that academic supervision contributes significantly to improving teacher professionalism and performance, and needs to be strengthened through reflective and continuous mentoring to ensure the sustainability of learning quality improvement.